Gempur Stunting dengan “Mie Aylor” di Desa Lewopao Kecamatan Ile Boleng - Reinaldis Masi; Mudmainna Mudmainna; Brigita Elisabet KR. Uran (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Stunting is a chronic nutritional problem that is still a public health challenge in various regions of Indonesia, including Lewopao Village, Ile Boleng District. This community service activity aims to educate the public about the importance of balanced nutrition and efforts to prevent stunting through nutritious local food innovations. One of the innovations introduced is "Mie Aylor" (short for Mie Ayam Lokal Organik), which is made from nutritious local ingredients such as moringa leaves, purple sweet potatoes, and mocaf flour. The activity methods include socialization, demonstrations of making noodles, and distribution of samples to the target community, especially pregnant women and mothers of toddlers. The results of the activity showed that the community was very enthusiastic about this product and understood the importance of nutrition in preventing stunting. This activity is expected to trigger public awareness in utilizing the potential of local food to support optimal child growth and development.